Pengendalian Kualitas Produk Kayu di CV. Berdikari Sukses dengan Menggunakan Metode Seven Quality Tools - Riskhi Aji Prastiyo; Akhmad Wasiur Rizqi; Muhammad Jufriyanto (Jurnal Serambi Engineering, 2023)
The objective of this research is to select a high-quality product for a successful self-released CV and reduce a non-high-quality product to a successful independent CV during the production process. Success is a company that works in the industry of building goods made of wood. Products made include wooden floors, wood for building materials, handrails, door frames, and floors with deck. There are seven major quality control tools that can be used to control quality. These include sheet checks, histograms, control charts, pareto diagrams, fishbone diagram, scatter diagrammes, and stratification. When a processed wood is rotated, there are three types of damage that can occur: monocular or perforated damage, damaged damage in the middle part, and hard damage. The biggest damage is border or hole damage, which accounts for 47.19 percent of the total damage. The inability of wood products to break. The total damage percentage is 13481, with an intermediate rupture of 30.55% and the lowest resistance result of 22.24%.